Ekonomi Sosial Kehidupan Anak Koin Di Pelabuhan Bakauheni - Kalam, Abdi; Ekawati, Farida; Husada, Hindiana Sava (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2024)
The lives of coin boys at Bakauheni Port have been of deep concern in this study. These children engage in dangerous activities such as diving into the sea to pick up coins thrown by ship passengers as their source of income. This research aims to investigate the social economy of the lives of coin boys in Bakauheni Harbor. The research methods used include interviews, observation, and quantitative data analysis. The results show that education, parents' occupation, family financial condition, and childhood living environment close to the port are the main factors that encourage children to become coin collectors. Although this activity is considered illegal and high-risk, children still do it to help their family finances and as a source of income. In addition, this study also relates its results to previous studies that have similar findings on the phenomenon of coin children in other ports. The conclusion of this study emphasizes the need for special attention to the issue of child coins and the importance of efforts from various parties, including the government, community, and family, to prevent children from engaging in such dangerous activities and restore their rights as children. The implications of this research are expected to contribute to further understanding of the issue of child coins and support efforts to prevent and protect children's rights.